2022
DOI: 10.1007/s10570-022-04769-2
|View full text |Cite
|
Sign up to set email alerts
|

Structural and chemical characterization of lignin and hemicellulose isolated from corn fibers toward agroindustrial residue valorization

Abstract: AIL) determination using UV spectrophotometry and Py-GC-MS. Hemicellulose was obtained after aqueous extraction, lipid removal, delignification and alkaline extraction. The isolated hemicellulose from CF confirmed the presence of arabinoxylan, which was similar to the results reported in the literature. The CF contained 8.0% and 4.0% ASL and AIL, respectively. Regarding lignin, the study identified more than 47 primary pyrolysis products for ASL, with 17%, 20% and 59% relative molar abundance for lignin, carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Nuclear magnetic resonance (NMR) and X-ray photoelectron spectrometry (XPS) could provide the organic skeleton information, including C/H atom distribution, aromaticity, and heteroatom bonding characteristics. , Fourier transform infrared (FTIR) spectrometry is helpful in understanding the distribution change of organic functional groups . For destructive techniques, thermogravimetric analysis (TGA) can be used to evaluate the thermochemical changes of LCBM during depolymerization, while gas chromatography/mass spectrometry (GC/MS) and high-resolution MS are helpful for understanding the group component distribution of derived soluble portions (SPs), including CH , >C al -O-, >C ar -O-, >CO, and N/S-containing classes. , Recent studies have shown that more comprehensive physicochemical structure information on LCBM and its derivatives can be obtained through the complementary advantages of non-destructive and selective destructive tools . Li et al .…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear magnetic resonance (NMR) and X-ray photoelectron spectrometry (XPS) could provide the organic skeleton information, including C/H atom distribution, aromaticity, and heteroatom bonding characteristics. , Fourier transform infrared (FTIR) spectrometry is helpful in understanding the distribution change of organic functional groups . For destructive techniques, thermogravimetric analysis (TGA) can be used to evaluate the thermochemical changes of LCBM during depolymerization, while gas chromatography/mass spectrometry (GC/MS) and high-resolution MS are helpful for understanding the group component distribution of derived soluble portions (SPs), including CH , >C al -O-, >C ar -O-, >CO, and N/S-containing classes. , Recent studies have shown that more comprehensive physicochemical structure information on LCBM and its derivatives can be obtained through the complementary advantages of non-destructive and selective destructive tools . Li et al .…”
Section: Introductionmentioning
confidence: 99%
“…As a natural carbohydrate polymer, it is the most abundant bioresource on Earth and can be derived from plants, animals, or bacteria (Babaei-Ghazvini et al, 2022). Cellulose are widely used to prepare many valuable products like nanostructured biocomposites, tough hydrogels, aerogel membranes, transparent paper, and lms (Barbosa et al, 2022;Thongsomboon et al, 2018). Among these, the corn stalk is an annually renewable lignocellulosic biomass, and most corn stalk yield is underutilized in China (Yang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%